Multiple Large Splenic Abscesses Managed with Computed Tomography-guided Percutaneous Catheter Drainage in Children - Jung Sook Yeom; Ji Sook Park; Ji-Hyun Seo; Eun Sil Park; Jae-Young Lim; Chan Hoo Park; Hyang Ok Woo; Jung Je Park; Jae Min Cho; Hee-Shang Youn (Elsevier, 2013)
Splenic abscess is a rare finding in children. Splenectomy combined with broad-spectrum antibiotics has been the treatment of choice for multiple splenic abscesses. Herein, we report the case of a 14-year-old girl with multiple large splenic abscesses that were successfully managed after two image-guided percutaneous drainage procedures and administration of intravenous antibiotics. Initially, an abscess located at the periphery in the lower pole of the spleen was aspirated under ultrasound guidance. Finally, another abscess located near the hilum of the spleen was drained under computed tomography guidance. To the best of our knowledge, this is the first report of multiple large splenic abscesses treated with computed tomography-guided percutaneous drainage.